State unemployment insurance reserves are not adequate - Christopher J. O'Leary; Kenneth J. Kline (W.E. Upjohn Institute for Employment Research, 2020)
Regular unemployment insurance (UI) benefits are paid from reserves held in state accounts at the U.S. Treasury. The Great Recession exhausted the majority of UI reserve accounts, and not all states have rebuilt reserves. We examine the adequacy of current state and systemwide UI reserves to weather a mild, moderate, or severe recession in the coming months. Our results suggest that a recession as severe as the average of those occurring since 1975 would cause 18 states to exhaust UI reserves. Our simulations account for the fact that several states have cut benefit generosity since the Great Recession ended. Results suggest that despite federal incentives for forward funding, reserves are insufficient in many states. By accepted standards, state benefit provisions are not excessive, but state-imposed constraints on financing make the system slow to recover from debt. We suggest modest actions for UI financing reform.
Keywords: H71; H81; J65; 330; Unemployment insurance; benefit financing; forward funding; taxable wage base; reserve ratio; adequate reserves; average high-cost rate; federal loans; state revenue bonds